2021
DOI: 10.1021/acs.chemrev.0c01177
|View full text |Cite
|
Sign up to set email alerts
|

Translational Applications of Hydrogels

Abstract: Advances in hydrogel technology have unlocked unique and valuable capabilities that are being applied to a diverse set of translational applications. Hydrogels perform functions relevant to a range of biomedical purposesthey can deliver drugs or cells, regenerate hard and soft tissues, adhere to wet tissues, prevent bleeding, provide contrast during imaging, protect tissues or organs during radiotherapy, and improve the biocompatibility of medical implants. These capabilities make hydrogels useful for many di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
432
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 630 publications
(432 citation statements)
references
References 644 publications
0
432
0
Order By: Relevance
“…PNP hydrogels of different formulations exhibit tunable shear-thinning, self-healing, yield-stress, and viscoelastic properties that enable them to create a lubricious barrier between organs and tissues that reduces the incidence and severity of adhesions. 22 – 24 We have previously demonstrated that hydrogels that are too soft and weak flow too easily when perturbed in the body, leaving target tissues too quickly while adhesions are still developing. Hydrogels that are too stiff are easily dislodged from target tissues as the yield stress of such materials exceeds their adhesion strength to the tissue.…”
Section: Resultsmentioning
confidence: 99%
“…PNP hydrogels of different formulations exhibit tunable shear-thinning, self-healing, yield-stress, and viscoelastic properties that enable them to create a lubricious barrier between organs and tissues that reduces the incidence and severity of adhesions. 22 – 24 We have previously demonstrated that hydrogels that are too soft and weak flow too easily when perturbed in the body, leaving target tissues too quickly while adhesions are still developing. Hydrogels that are too stiff are easily dislodged from target tissues as the yield stress of such materials exceeds their adhesion strength to the tissue.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the implantable form, an injectable hydrogel has shown impressive therapeutic effects as a carrier for cancer vaccine and anti-PD-1 monoclonal antibodies ( Li et al, 2020 ). A recent review covers this area in depth from the hydrogel materials, therapeutic strategies as well as clinical perspectives ( Correa et al, 2021 ).…”
Section: Moving Towards Clinical Translationmentioning
confidence: 99%
“…Polymeric structures importantly allow for local and/or sustained release of active therapeutics and have been long a subject of investigation in gliomas, particularly as implants in the post-resection cavity [45][46][47][48][49][50][51][52][53][54]. BCNU wafers were approved for local delivery of carmustine to the glioma resection cavity in 1996, leading the pack on implantable local therapeutics for brain tumors [55,56].…”
Section: Polymeric Structures and Hydrogelsmentioning
confidence: 99%